Debilitating Periorbital Edema Secondary to Anti-SAE Dermatomyositis - Gayane Matusov; Toan Do; Richard Keating; Geva Mannor; Andrew White (Annals of Internal Medicine: Clinical Cases)
Dermatomyositis (DM) is an autoimmune inflammatory myopathy with heterogeneous systemic and cutaneous manifestations. Certain forms of DM have isolated skin findings without overt myositis and are called amyopathic DM. Myositis-specific autoantibodies are associated with distinct phenotypes of DM that can support the diagnosis and better define management and prognostication. We describe a case of amyopathic DM with the presence of the small ubiquitin-like modifier activation enzyme 1 autoantibody presenting with severe, debilitating periorbital edema.